2019
DOI: 10.1001/jamanetworkopen.2019.9261
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Age Distribution of Obesity-Associated Cancers

Abstract: This cross-sectional study examines temporal shifts in age distribution of obesity-associated cancers and non–obesity-associated cancers across race/ethnicity- and sex-specific strata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…The prevalence of obesity has doubled since 1980, with almost one-third of the global population now classified as overweight or obese. ( Afshin et al., 2017 ; Koroukian et al., 2019 ) Obesity constitutes a significant public health issue given its adverse effect on physiological function. Compounding this, over the last decades there has also been a profound shift in the aging demographic, with a substantial increase in life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of obesity has doubled since 1980, with almost one-third of the global population now classified as overweight or obese. ( Afshin et al., 2017 ; Koroukian et al., 2019 ) Obesity constitutes a significant public health issue given its adverse effect on physiological function. Compounding this, over the last decades there has also been a profound shift in the aging demographic, with a substantial increase in life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Increasing childhood obesity is a matter of grave concern as it has shifted the burden of cancer to younger age groups. [5] In addition, being overweight before the age of 40 increases the risks of various ORCs by 15%. The study from Bergen (Norway) showed increased risk of cancers of the endometrium (by 70%), renal cancer in males (by 58%), and colon cancer in male (by 29%).…”
Section: Obesity-related Cancersmentioning
confidence: 99%
“…pancreatic, prostate, and breast cancer). [8][9][10] Indeed, PA serves as energy sources for cancer growth, significantly promoting cancer cell invasiveness and metastatic potential [11][12][13] and, consistently, increased levels of PA have been observed in the plasma of cancer patients. 14 Autophagy is a lysosomal-dependent degradation process required for the maintenance of cellular and tissue homeostasis.…”
Section: Introductionmentioning
confidence: 99%